Performance of code position modulation for 2.4GHz IEEE 802.15.4 PHY in indoor multipath channels. - Marciano, Joel S., Jr.
This paper provides an introduction to the IEEE 802.15.4 standard, which specifies the physical (PHY) and personal area networking (LR-WPAN) communication systems. We also present results of simulations representing our initial efforts in characterizing the performance of the physical layer (PHY) of the IEEE 80.15.4 Wireless Personal Area Network (WPAN) Standard in wireless channel characterized by multipath propagation and additive white Gaussian noise (AWGN). In particular, the studies are conducted on the 2.4GHz PHY, which specifies code position modulation (CPM) to achieve spectrum spreading of a maximum 250kbps data over a transmission bandwidth of 2MHz. A simple code correction technique using a look-up table was implemented at the receiver and the bit error rate (BER) is calculated for the JTC residential, commercial and office multipath propagation models. The results indicate that CPM provides a performance gain of between 4-11dB over conventional narrowband signaling at moderate signal-to-noise-ratio-per-bit levels. We also present a summary of development activities conducted at the Communications Engineering Laboratory (CEL) of the Department of Electrical and Electronics Engineering of the University of the Philippines Diliman (UP EEE) in the area of LR-WPAN.
Keywords: Multipath propagation; WPAN; Zigbee